Gross Anatomical Studies on the Tongue of White Leghorn - Shikha Saini, (Indian Journal of Veterinary Anatomy, 2022)
In the present study, tongues of twenty five female adult White Leghorn birds were used. The tongue waslocated on the floor of the oro-pharyngeal cavity in a depression between the mandibular rami and directeddownwards and backwards. The tongue was triangular in outline, roughly arrowhead shaped with pointed tip. Itwas pinkish-white in colour. The tongue was distinguished into three regions- the apex, body and the root (radix).The apex was sharp, pointed and free. The rostral half was free. Apapillary crest comprising of a row of caudallydirected papillae was present between the root and the body, having around 27-30 papillae. Ashort row of three tofour papillae extended caudally from the edges of the papillary crest bilaterally. The caudal of the tongue wasconnected with the floor of the oropharynx by frenulum linguae.